1998
DOI: 10.1093/hmg/7.1.121
|View full text |Cite
|
Sign up to set email alerts
|

Truncated Forms of the Androgen Receptor are Associated with Polyglutamine Expansion in X-Linked Spinal and Bulbar Muscular Atrophy

Abstract: X-linked spinal and bulbar muscular atrophy (SBMA) is a rare form of motor neuron degeneration linked to a CAG repeat expansion in the first exon of the androgen receptor gene coding for a polyglutamine tract. In order to investigate the properties of the SBMA androgen receptor in neuronal cells, cDNAs coding for a wild-type (19 CAG repeats) and a SBMA mutant androgen receptor (52 CAG repeats) were transfected into mouse neuroblastoma NB2a/d1 cells. The full length androgen receptor proteins, of 110-112 kDa an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
0

Year Published

1999
1999
2006
2006

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(44 citation statements)
references
References 52 publications
2
42
0
Order By: Relevance
“…AR with expanded polyglutamine repeats has been implicated in neurodegenerative disease wherein AR is cleaved between the DBD and LBD into a toxic, ''truncated'' ATD-DBD moiety (18). Caspase-3 is suggested to be the enzyme responsible for the cleavage of this pathologic AR (19)(20)(21)(22).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…AR with expanded polyglutamine repeats has been implicated in neurodegenerative disease wherein AR is cleaved between the DBD and LBD into a toxic, ''truncated'' ATD-DBD moiety (18). Caspase-3 is suggested to be the enzyme responsible for the cleavage of this pathologic AR (19)(20)(21)(22).…”
Section: Discussionmentioning
confidence: 99%
“…Other studies (11) established that proteolysis can cleave AR into two fragments: one of f50 kDa containing both the LBD and the DBD and another of approximately the same size, presumably the ATD (13). Third, the caspase family of thiol proteases is capable of cleaving AR, particularly those forms of AR with expanded polyglutamine repeats (18)(19)(20)(21)(22). To date, the cleavage of AR by the Ca 2+ -activated, thiol protease calpain has not been described.…”
Section: Introductionmentioning
confidence: 99%
“…3 The gene normally has 10-36 CAG repeats, 4 but in SBMA patients the number of repeats is increased to 38-72. 5,6 Several other neurodegenerative disorders caused by trinucleotide repeat expansions have also been reported. [7][8][9] It has been shown that proteins with expanded polyglutamine stretches encoded by the CAG repeats form fibrillary aggregates in neurones, leading to apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…10 Such aggregates have also been reported in SBMA. 4,6,11 The human AR gene is located in Xq11-q12. The gene contains 8 exons.…”
Section: Introductionmentioning
confidence: 99%
“…As observed in vivo, mutant huntingtin and other disease proteins containing expanded polyglutamine tracts form aggregates in vitro, whereas wildtype proteins with a normal tract do not (Lunkes & Mandel 1998;Igarashi et al 1998;Skinner et al 1997;Ellerby et al 1999a;Hackam et al 1998a;Cooper et al 1998;Butler et al 1998;Merry et al 1998;. Aggregates formed in vivo and in vitro are frequently ubiquitinated (Lunkes & Mandel 1998;Cooper et al 1998;Igarashi et al 1998;Cummings et al 1998;A.…”
Section: (B) the Cell Culture Model Can Mimic In Vivo Eventsmentioning
confidence: 99%